Collaboration of Islamic and Christian Teachers in Implementing Religious Moderation Education - Sinaga, Ali Imran; Dalimunthe, Rasyid Anwar; Daulay, Saripuddin (Pascasarjana Universitas KH. Abdul Chalim, 2023)
This article aims to reveal the collaboration of Islamic and Christian religious teachers in SMA/SMK in the Pantai Labu District. The method used is descriptive research with a field approach and data analysis named after Miles and Huberman. The research results found were [1]. The activity of combining students in one group to clean houses of worship, both mosques and churches, has been carried out by Islamic and Christian religious teachers. The target is of course to provide experience and habituation for students to do together in every social activity, [2]. If there are friends and parents of grieving students, Islamic and Christian religious teachers always combine Muslim and Christian students to attend the visit. [3]. If any of the students are experiencing grief, the Islamic and Christian religion teachers direct students to give their sincerity in collecting the finances that will be given to the grieving students without discriminating between race, ethnicity, and religion owned by each student. [4]. Familiarize students to support each other in completing the equipment needed for the activities of religious holidays. [5].Inviting each other to religious holidays. The implication of this article can be a guide for religious teachers in multicultural Education in their respective schools. It can open up space for thoughts if teachers are contaminated with narrow thinking.